A new method for isolating the bronchial arteries in closed chested dogs : reflex bronchoconstriction and apnoea caused by histamine injected into the bronchial arteries - De Kock, M. A (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Med) - University of Stellenbosch, 1964.